Identification of a prognostic evaluator from glutamine metabolic heterogeneity studies within and between tissues in hepatocellular carcinoma - Bao, Jie; Yu, Yan (Frontiers in Pharmacology, 2023)
The liver is the major metabolic organ of the human body, and abnormal metabolism is the main factor influencing hepatocellular carcinoma (HCC). This study was designed to determine the effect of glutamine metabolism on HCC heterogeneity and to develop a prognostic evaluator based on the heterogeneity study of glutamine metabolism within HCC tumors and between tissues.Single-cell transcriptome data were extracted from the GSE149614 dataset and processed using the Seurat package in R for quality control of these data.. HCC subtypes in The Cancer Genome Atlas (TCGA) and the GSE14520 dataset were identified via consensus clustering based on glutamine family amino acid metabolism (GFAAM) process genes. The machine learning algorithms Gradient Boosting Machine, Support Vector Machine, Random Forest, eXtreme Gradient Boosting, Decision trees, and Least Absolute Shrinkage and Selection Operator were utilized to develop the prognosis model of differentially expressed genes among the molecular gene subtypes.The samples in the GSE149614 dataset included 10 cell types, and there was no significant difference in the GFAAM pathway. HCC was divided into three molecular subtypes according to GFAAM process genes, showing molecular heterogeneity in prognosis, clinicopathological features, and immune cell infiltration. C1 showed the worst survival rate and the highest immune score and immune cell infiltration. A six-gene model for prognostic and immunotherapy response was constructed among subtypes, and the calculated high-risk score was significantly correlated with poor prognosis, high immune abundance, and low response rate of immunotherapy in HCC.Our discovery of GFAAM-associated marker genes may help to further decipher the role in HCC occurrence and progression. In particular, this 6-gene prognostic model may serve as a predictor of treatment and prognosis in HCC patients.